PENGEMBANGAN MEDIA PEMBELAJARAN GAME EDUKASI ROLE PLAYING GAME (RPG) UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATERI PENCEMARAN LINGKUNGAN - Ferryan Sandi (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Abstract: Natural science is a science that studies natural phenomena using a scientificapproach and is taught in an integrated manner at the level of junior high schooleducation. One of the topics in the junior high school science subject isenvironmental pollution. The environmental pollution topics can be accepted easilyif students can observe, feel, or experience them directly. At the location of thisresearch, the condition of the school environment is a clean and orderlyenvironment. This results in the lack of the phenomenon of environmentalpollution that can be used as a source of learning. In addition, the use of minimallearning media makes students less actively involved in learning so that studentsare less motivated in participating in learning. Therefore, this research wasconducted by developing learning media products in the form of RPG educationalgames on environmental pollution materials to increase students' learningmotivation. This type of research is research and development (R&D) with theADDIE development model. This research produces learning media products in theform of RPG educational games that are suitable for use with a media validationscore of 85.53 percent, material validation of 77.08percent, readability scores of 85.50percent and thelevel of student motivation to learn using RPG educational game learning media of82.11percent. Based on these results, it can be concluded that the learning media arevalid and feasible to use.